(untitled) (International Association of Biologicals and Computational Digest, 2023)
Nandigram Service Centre occupy 25 acres of total land. Nandigram Service Centre is the place which works for Rural People for their Rural development, health Services, cowshed, Farming, Education. Many Basidiomycetes fungi intermingled with other vascular plants. 20 types of Basidiomycetes fungi found in this Nandigram Service Centre. All Basidiomycetes fungi are showed, collected, stored in formaldehyde solution. They are identified by (Laessøe and Peterson, 2019) (Grace et al., 2019) (Kumar and Manimohan, 2009). Their Habitat also described in this. Occurrence of different family, Genus and species chart are also described. Agaricaceae family is dominant than other family found in Nandigram Service Centre and Ganoderma and Lepiota Genus are dominant other Genus available in Nandigram Service Centre. Nandigram Service Centre Most of the Basidiomycete’s fungi are showed in Soil.